Thermal Fatigue Life Prediction of Ventilation Air Methane Oxidation Bed - Liu, Y.Q.; Shang, Q.H.; Zhang, D.H.; Wang, Y.X.; Sun, T.T. (Проблемы прочности, 2016)
Thermal flow-reversal oxidation is the main technology that can effectively reduce emissions of ventilation air methane. As the core component of coal mine ventilation oxidation devices, honeycomb ceramic oxidation beds play a decisive role in the functionality of these devices. The thermal fatigue properties of mullite ceramic – which is commonly used in oxidation beds – was tested in the present research. Then, the service life of the oxidation bed was predicted according to the intensity attenuation law and the thermal fatigue experimental data. The results of the fatigue experiment indicated that in general, the bending strength of mullite ceramics decreases as thermal shocks increase. At higher temperature differences, the bending strength decreased at greater rates. At the temperature differences between 600 and 800°C, the bending strength initially declined. Then, after reaching a certain value, it remained unchanged for a while before declining again. The results of the equation that was developed from intensity attenuation theory and the thermal fatigue experimental data indicate that the thermal fatigue life of an oxidation bed is about 1–8 months. The predicted result is consistent with actual working conditions.